2004
DOI: 10.1523/jneurosci.5377-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Seizures Regulate Gene Expression of Distinct Neurotrophic Signaling Pathways

Abstract: Electroconvulsive therapy (ECT) remains the treatment of choice for drug-resistant patients with depressive disorders, yet the mechanism for its efficacy remains unknown. Gene transcription changes were measured in the frontal cortex and hippocampus of rats subjected to sham seizures or to 1 or 10 electroconvulsive seizures (ECS), a model of ECT. Among the 3500 -4400 RNA sequences detected in each sample, ECS increased by 1.5-to 11-fold or decreased by at least 34% the expression of 120 unique genes. The hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
233
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(247 citation statements)
references
References 50 publications
9
233
0
5
Order By: Relevance
“…These include BDNF whose transcription is upregulated by both ECT and SD as previously reported, 13,21,[109][110][111] although unlike other studies 13,112 both microarray and ISH analysis demonstrated that BDNF transcription is not affected by FLX. Similarly, NTRK2 upregulation also confirm earlier reports that neutropin signaling is activated by antidepressant treatments.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…These include BDNF whose transcription is upregulated by both ECT and SD as previously reported, 13,21,[109][110][111] although unlike other studies 13,112 both microarray and ISH analysis demonstrated that BDNF transcription is not affected by FLX. Similarly, NTRK2 upregulation also confirm earlier reports that neutropin signaling is activated by antidepressant treatments.…”
Section: Resultsmentioning
confidence: 67%
“…Many studies have examined the effects of ECT on the CSF or serum level of selected markers including neurotransmitters, neuropeptide and hormones. [20][21][22][23] Similar work has been carried out on SD. Yet, no molecular and/or cellular mechanism has been identified that satisfactorily explains the rapid, although transient, antidepressant effects of ECT and/or SD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was reported that PI 3-kinase activity is decreased in occipital cortex of suicide subjects (Hsiung et al, 2003) and that ECS (Altar et al, 2004) or long-term lithium treatment (Chalecka-Franaszek and Chuang, 1999) increases PI 3-kinase activity. Given the role of PI 3-kinase in a plethora of biological functions, these and our present findings appear to be quite significant and suggest the possibility that dysfunction of PI 3-kinase signaling may be important in the pathophysiologic mechanisms of suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic administration of antidepressants increases BDNF expression in the hippocampus 17,18 BDNF has antidepressant-like activity in learned helplessness paradigms and the forced swim test 19 Environmental stressors decrease central BDNF mRNA 8 Higher BDNF levels in the frontal cortex, occipital cortex, and hypothalamus of the 'depressed' FSL animals relative to the FRL controls 20 Decreased central BDNF in models of stress-induced depression 17,21,22 Downregulation of the Trk-B signaling pathway in the genetic animal models of depression 23 ECS, used as an ECT model, increases BDNF in the hippocampus, striatum, and occipital cortex 24 Lithium increases the expression of BDNF in the hippocampus and cortex of rats 25 BDNF in schizophrenia and depression F Angelucci et al tissue from schizophrenic subjects and MRI data in vivo suggest ongoing specific neurodegeneration. 43 There is also strong evidence suggesting that nonheritable factors in the pathogenesis of schizophrenia are associated with abnormalities during prenatal development.…”
Section: Animal Modelsmentioning
confidence: 99%
“…37 Electroconvulsive treatment (ECT), effective in treatment-resistant schizophrenia in combination with neuroleptics, 61 also upregulates the expression of BDNF. 62,18 For these reasons, in addition to providing a link between neurodevelopmental and neurodegenerative phenomena, BDNF is an attractive candidate target molecule in the treatment of schizophrenia.…”
Section: Animal Modelsmentioning
confidence: 99%